Mito-nuclear sequencing is paramount to correctly identify sympatric hybridizing fishes - Sousa-Santos, Carla (2018)
Background. Hybridization may drive speciation and erode species, especially when intrageneric sympatric species are involved. Five sympatric Luciobarbus species—Luciobarbus sclateri (Günther, 1868), Luciobarbus comizo (Steindachner, 1864), Luciobarbus microcephalus (Almaça, 1967), Luciobarbus guiraonis (Steindachner, 1866), and Luciobarbus steindachneri (Almaça, 1967)—are commonly identified in field surveys by diagnostic morphological characters. Assuming that i) in loco identification is subjective and observer-dependent, ii) there is previous evidence of interspecific hybridization, and iii) the technical reports usually do not include molecular analyses, our main goal was to assess the concordance between in loco species identification based on phenotypic characters with identifications based on morphometric indices, mtDNA only, and a combination of mito-nuclear markers. Materials and methods. Specimens of Luciobarbus from six Guadiana River sub-basins were collected and sequenced for the cytochrome b and beta-actin genes. For comparative purposes, samples of Luciobarbus from other 12 river basins were also used. Four levels of taxonomical identification were conducted based on: identification made in the field (in loco identification), cytb gene only, beta-actin gene only, and mito-nuclear combined genomes. Results. Results showed that interspecific hybridization seems to be high (around 41%) and likely favoured by non-random mating and the loss of fluvial connectivity. About 34% of the hybrids showed mito-nuclear discordance. Misidentifications were frequent when only phenotypic characters are considered, and the use of a single mitochondrial gene is not sufficient: the use of two mito-nuclear markers showed that around 82% of the in loco identifications based on the phenotype were not correct. Conclusion. Incorrect species assignment likely generated biased results in previous studies on the biology and ecology of Guadiana barbels and in the assignment of conservation status and, consequently, on the establishment of conservation management measures